A direct comparison of linear and star-shaped poly(dimethylaminoethyl acrylate) polymers for polyplexation with DNA and cytotoxicity in cultured cell lines. (February 2017) - Liao, Xin; Walden, Grace; Falcon, Noelia D.; Donell, Simon; Raxworthy, Michael J.; Wormstone, Michael; Riley, Graham P.; Saeed, Aram
Graphical Abstract: Highlights: Effect of linear and star-shaped cationic polymers on DNA binding and cytotoxicity. Star-shaped polymer form polyplex at smaller N/P ratio than linear counterparts. Molecular weight of the cationic polymers is a determinant of cytotoxicity. Abstract: Poly[2-(Dimethylamino) ethyl acrylate] (PDMAEA) based polymers have been studied as potential gene delivery system. However, few reports emerging in literature suggesting that star-shaped PDMAEA based polymers are performing better in polyplexation with DNA, cytotoxicity and transfection, as compared to linear counterparts. Nonetheless, little evidences exist on direct comparison between the linear and star-shaped polymer structures. To address this, a series of new star-shaped PDMAEA polymers with linear counterparts were synthesised and directly compared their polyplexation with DNA and cytotoxicity in culture cell lines. The star-shaped PDMAEA polymers were synthesised using pentaerythritol tetrakis [2-(dodecylthiocarbonothioylthio)-2-methylpropionate] (4-arm DDMAT) RAFT agent in a "core-first" approach, whereas 2-(dodecylthiocarbonothioylthio)-2-methylpropionate was used to synthesise linear PDMAEA polymers. In order to investigate the effect of molar mass, both star-shaped and linear PDMAEA were synthesised in low (10 kDa) and high (20 kDa) molar mass. It must be noted here that the overall molar mass of the star-shaped polymer was equal to that of the linear counterparts. Interestingly, we found that the star-shaped polymer has slightly smaller hydrodynamic diameter (more compact) relative to linear counterparts, and importantly, star-shaped PDMAEA binds to DNA at much lower nitrogen to phosphate ratio (N/P ratio). However, the cytotoxicity studies in cultured 3T3 murine cell lines demonstrated that both star-shaped and linear counterparts have no toxicity at low 10 kDa, but significantly toxic at higher 20 kDa molar mass, this finding confirmed that the molar mass of PDMAEA play a key role in cytotoxicity effect, not variable polymer structures. Taken together, star-shaped PDMAEA binds more effectively to DNA than linear counterparts and showed no toxicity at 10 kDa molar mass at variable polymer concentrations.